Paul Unbound other perspectives on the Apostle - Given, Mark Douglas 1961- (Emory studies in early Christianity, 2022)
"The essays in this second edition of Paul Unbound: Other Perspectives on the Apostle serve as an introduction for advanced undergraduate and graduate students to Paul's relationship to the Roman Empire, the economy, his opponents, ethnicity, the law, Judaism, women, and Greco-Roman rhetoric. Contributors Warren Carter, Charles H. Cosgrove, A. Andrew Das, Steven J. Friesen, Mark D. Given, Deborah Krause, Mark D. Nanos, and Jerry L. Sumney have expanded their original essays and updated the bibliography to take into account scholarship produced in the decade since the publication of the first edition"--